Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (Tai) Terhadap Pemahaman Konsep Matematis Peserta Didik Kelas VIII SMPN 1 2x11 Kayutanam - EFRI YANTI (Departemen Matematika, 2019)
Understanding mathematical concepts is one of the goals of mathematics learning that must be achieve by student. But in reality the understanding of mathematical concepts of student in class VIII of SMPN 1 2x11 Kayutanam is still can be improve because learning activities in schools have not facilitated students to improve their understanding of mathematical concept. One effort that can be used to overcome these problems is to apply the Team Assisted Individualization type of cooperative learning model. The type of this research is quasy-experiment and descriptive research design with Randomized Control Group Only Design. Based on the results of data analysis, it was concluded that understanding the mathematical concepts of students learning by using Team Assisted Individualization type cooperative learning models is better than understanding mathematical concepts of students learning by direct learning in class VIII SMPN 1 2x11 Kayutanam. Then, the development of students' mathematical concept understanding during the Team Assisted Individualization type cooperative learning model has increased. Keywords – Cooperative learning, team assisted individualization, understanding of mathematical concept